Characterization of hepatocellular carcinoma (HCC) lesions using a novel CT-based volume perfusion (VPCT) technique. Issue 6 (June 2015) - Kaufmann, S.; Horger, T.; Oelker, A.; Kloth, C.; Nikolaou, K.; Schulze, M.; Horger, M.
Highlights: Quantification of perfusion with VPCT has great potential for functional imaging. We present our preliminary results of perfusion parameters (Blood Flow, Blood Volume and kk-trans) of hepatocellular carcinoma (HCC) in terms of using VPCT and two different calculation methods, compare their results and look for correlation between tumor arterialization and lesion size. VPCT can measure tumor volume perfusion non-invasively and enables quantification of the degree of HCC arterialization. Results are dependent on the technique used with best inter-method correlation for Blood Flow. Tumor arterialization did not proved size-dependent. Abstract: Objective: To characterize hepatocellular carcinoma (HCC) in terms of perfusion parameters using volume perfusion CT (VPCT) and two different calculation methods, compare their results, look for interobserver agreement of measurements and correlation between tumor arterialization and lesion size. Material and methods: This study was part of a prospective monitoring study in patients with HCC undergoing TACE, which was approved by the local Institutional Review Board. 79 HCC-patients (mean age, 64.7) with liver cirrhosis were enrolled. VPCT was performed for 40 s covering the involved liver (80 kV, 100/120 mAs) using 64 mm × 0.6 mm collimation, 26 consecutive volume measurements, 50 mL iodinated contrast IV and 5 mL/s flow rate. Mean/maximum blood flow (BF; ml/100 mL/min), blood volume (BV) and k -trans were determined both with the maximum slope + Patlak vs. deconvolution method. Additionally, the portal venous liver perfusion (PVP), the arterial liver perfusion (ALP) and the hepatic perfusion index (HPI) were determined for each tumor including size measurements. Interobserver agreement for all perfusion parameters was calculated using intraclass correlation coefficients (ICC). Results: The max. slope + Patlak method yielded: BFmean/max = 37.8/57 mL/100 g-tissue/′, BVmean/max = 9.8/11.1 mL/100 g-tissue, k -trans-mean/max = 34.4/44.5 mL/100 g-tissue/′. For the deconvolution method BFmean/max, BVmean/max and, k -trans-mean/max were 68.3/106.1 mL/100 g-tissue/′, 12.6/15.5 mL/100 g-tissue and 24/33.8 mL/100 g-tissue/′. Mean ALP, PVP, HPI and size were 53.7 mL/100 g-tissue/′, 2.4 mL/100 g-tissue/′, 96.4 and 3.5 cm, respectively. Interobserver agreement measured with intraclass coefficient correlation (ICC) was very good for all perfusion parameters (≥0.99). Best correlation between calculation methods was achieved for measurements of BF, while BV and k -trans values were less correlated. There was no relationship between HPI and lesion size. Conclusion: VPCT can measure tumor volume perfusion non-invasively and enables quantification of the degree of HCC arterialization. Results are dependent on the technique used with best inter-method correlation for BF. Tumor HPI did not proved size-dependent.